Developing geriatric face makeup enrichment book for students of Skin Beauty program in vocational high school - Pramesti Adika Ratri; Siti Hamidah (Universitas Negeri Yogyakarta, 2020)
This study aims to produce a proper and effective Geriatric Makeup book as enrichment material for beauty students at Vocational School. This study used a research and development approach with a Four-D model. This model consists of four steps of development; they are Define, Design, Develop, and Disseminate. The product feasibility test was carried out by two material experts and two media experts. The feasibility test results were subsequently tested for agreement between experts through Cohen's Kappa coefficient test. The book's effectiveness was seen by the gain score when implemented using a quasi-experimental design with a one-group case study. The research subjects were 28 students of the XI beauty class of SMK N 3 Purworejo. The data collection instrument were observation guidelines, interview guidelines, expert validation sheets, student response questionnaires, and ability tests. The study results show that the enrichment book fulfills the eligibility criteria based on the expert material with a score of 3.59 (very good). According to the expert, there was an agreement between experts of 0.64 (good) and fulfilled the eligible criteria with a score of 3.70 (very good). There was an agreement between expert 1.00 (very good). The developing enrichment book was effective to be used by beauty class XI students SMK Negeri 3 Purworejo with an understanding gain score of 0.5 (moderate) and with a skill gain score of 0.71 (high).